Rent-Seeking and Corruption in the Granting of Oil Palm Plantation Land Cultivation Rights (HGU): A Case Study of PT Permata Hijau Pasaman Unit II in Nagari Maligi, West Pasaman Regency, Indonesia - Afif Wardana (Journal of Social and Policy Issues, 2026)
This study examines the mechanisms of rent-seeking and structural corruption in the allocation of Land Cultivation Rights (Hak Guna Usaha/HGU) for the oil palm plantation of PT Permata Hijau Pasaman (PHP) Unit II in Nagari Maligi, Sasak Ranah Pasisia District, West Pasaman Regency, Indonesia. The study addresses an important gap in the literature by exploring how customary institutions are co-opted as mediating actors within agrarian patronage networks, a dimension that has received limited scholarly attention. Employing a qualitative approach with a single-case study design, data were collected through in-depth interviews with 20 purposively selected informants, passive participant observation, and documentary analysis. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal four principal mechanisms of institutionalized rent-seeking and corruption. First, customary authority was commodified through a divide-and-rule strategy that fragmented indigenous community solidarity and weakened collective resistance. Second, the company's failure to fulfill its legal obligation to establish 1,453 hectares of plasma plantations represented a form of predatory capital accumulation, allowing economic benefits to be concentrated among corporate and political elites. Third, the study identifies the manipulation of HGU spatial data, involving approximately 400 hectares of land cultivated beyond the officially licensed concession, facilitated through falsified land measurement documents. Fourth, bureaucratic institutions normalized regulatory violations through a pattern of fragmented impunity, whereby overlapping institutional responsibilities obscured accountability and enabled persistent non-compliance. This study concludes that corruption in HGU licensing is fundamentally pre-decisional, emerging long before formal permits are issued through patronage alliances linking corporate actors, bureaucratic elites, and customary leaders. These networks shape administrative decisions, weaken regulatory oversight, and institutionalize unequal access to land. The study contributes to the literature on rent-seeking, institutional corruption, and agrarian governance by demonstrating that corruption extends beyond administrative malpractice to encompass the systematic capture of local institutions. The findings underscore the need for independent spatial audits, stricter enforcement of plasma plantation obligations, and the reconstruction of accountable customary governance to promote transparency, equity, and sustainable land governance.